Comparison of clinical outcomes of hydrofiber and standard dressings in postoperative knee and hip arthroplasty wounds: a comprehensive meta-analysis - Zhang, Ran; Sun, Rui (Frontiers in Surgery, 2025)
ObjectivesThe purpose of this study was to compare the clinical efficacy, safety and cost-effectiveness of hydrofiber dressings and standard dressings in the management of wounds after total knee or hip arthroplasty.MethodsThis meta-analysis was conducted according the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. We searched PubMed, EMBASE, and the Cochrane Library from inception to January 2025 to identify English-language randomized controlled trials (RCTs) and comparative cohort studies. Studies were included if they compared hydrofiber dressings with traditional or other standard dressings and involved patients undergoing primary hip or knee arthroplasty with an expected postoperative hospital stay of four days or more. The included studies were assessed for methodological quality. A meta-analysis and systematic review were performed on data extracted from these studies.ResultsNine RCTs with total 1,223 participants and three cohort studies with total 2,152 participants were included. The results showed that hydrofiber dressings significantly outperformed standard wound dressings in terms of blister formation (RR, 0.48; 95% CI, 0.27–0.87; P = 0.02; I2, 51%), periprosthetic joint infection (PJI) rate (RR, 0.27; 95% CI, 0.09–0.75; P = 0.01; I2, 0%), total complication rate (RR, 0.46; 95% CI, 0.29–0.75; P = 0.002; I2, 61%), number of dressing changes (MD, −1.87; 95% CI, −2.76 to −0.98; P < 0.0001; I2, 96%), and the need for dressing change within five days after surgery (RR, 0.55; 95% CI, 0.38–0.79; P = 0.001; I2, 43%). The systematic review showed that hydrofiber dressings were superior to standard wound dressings in terms of comfort and average total cost.ConclusionThe hydrofiber dressings were superior to standard wound dressings in terms of blistering, PJI rate, total complication rate, number of dressing changes, and need for dressing change within five days after surgery.